2007
DOI: 10.1139/h06-109
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary O2 uptake on-kinetics in sprint- and endurance-trained athletes

Abstract: Pulmonary O 2 uptake kinetics during ''step'' exercise have not been characterized in young, sprint-trained (SPT), athletes. Therefore, the objective of this study was to test the hypotheses that SPT athletes would have (i) slower phase II kinetics and (ii) a greater oxygen uptake ''slow component'' when compared with endurance-trained (ENT) athletes. Eight sub-elite SPT athletes (mean ( ± SD) age = 25 (±7) y; mass = 80.3 (±7.3) kg) and 8 sub-elite ENT athletes (age= 28 (±4) y; mass = 73.2 (±5.1) kg) completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…This prediction was confirmed by Paganini et al (49), who demonstrated that increased citrate synthase activity induced by endurance training resulted in faster [PCr] kinetics in rat muscle, and also by Glancy et al (16), who recently reported that increasing the content of isolated mitochondria in an incubation medium was associated with linear reductions in the for O 2 consumption. In humans, it is well known that V O 2 kinetics are faster (5,6,36,39,50) and that the extent of PCr splitting for a given work rate is spared (23,29,70) in endurance-trained subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This prediction was confirmed by Paganini et al (49), who demonstrated that increased citrate synthase activity induced by endurance training resulted in faster [PCr] kinetics in rat muscle, and also by Glancy et al (16), who recently reported that increasing the content of isolated mitochondria in an incubation medium was associated with linear reductions in the for O 2 consumption. In humans, it is well known that V O 2 kinetics are faster (5,6,36,39,50) and that the extent of PCr splitting for a given work rate is spared (23,29,70) in endurance-trained subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the parameters of the power–time relationship are related to other markers of cardio-respiratory fitness [37]. Of particular note is that, across subjects, CP is related to fast on-kinetics [38] and W ′ is related to the magnitude of the slow component [17, 38].…”
Section: The Cp Concept and Variable-pace Exercisementioning
confidence: 99%
“…This phenomenon is known as the slow component of V ・ O2 16) . However, in well-trained endurance runners, V ・ O2 attains a steady state faster and the slow component is smaller than that observed in sprinters 17,18) . This suggests that high-intensity RE could be evaluated in distance runners with superior aerobic capacity.…”
Section: Introductionmentioning
confidence: 63%
“…However, the slow component of V ・ O2 is smaller in well-trained endurance runners and their V ・ O2 reaches a steady state faster than that in sprinters 17,18) . Indeed, in the present study, the subjects' V ・ O2 reached a steady state (changing by less than 100 mLO2·min −1 ) 25) even at an intensity above the LT.…”
Section: Discussionmentioning
confidence: 89%